Overcoming Intercultural Obstacles in Translation (Dristikon: A Multidisciplinary Journal, 2023)
One major obstacle in the process of translation is the transfer of culture from the source text to the translated one. The source text’s language naturally carries the culture where it is used both in life and writing.  So is the case of the language used in the translated text. Here lies the problem of cultural transfer from the source to the translated text. This article deals with the same problem in general and the transfer of Nepali text into English in particular. Currently, available theories of translation and their focus in regard to the obstacles of transferring the culture through translation and their possible solutions have been reviewed as the theoretical support for the discussion. The examples have been supplied from different languages and their translation with a major focus on the translation of Nepali text into English and vice-versa. This article will be useful for the researchers of Nepali translation into English and other languages.